The making of the port landscape in Roman Africa : from Alexandrian influence to African originality - (:unkn) unknown (My University, 2019)
The fabric of the Roman port landscape is a process that has been nourished by many influences. From its Alexandrine origin, the port image benefits from the contribution of a new landscape aesthetic, topographical art and the diffusion of a canonical image conveyed by the Aeneid. This original synthesis flourishes in the Roman provinces of Africa.
Keywords: African Research